Russia - Public Expenditure Review - World Bank (World Bank, 2012)
The primary objective of the Public Expenditure Review (PER) is to assist the Ministry of Finance (MOF) in identifying opportunities for efficiency gains in some key categories of government expenditure. In this context, policy makers face two related fiscal dilemmas. First, how can expenditure efficiency are increased to provide public services with fewer resources? Second, how can the fiscal space for key infrastructure investments are increased to ensure an enabling environment for long-term growth and diversification? To answer these questions, this PER analyzes three closely interrelated topics: a) aggregate fiscal discipline and overall public expenditure management, b) public expenditures in transport with specific focus on roads and railways, and c) public employment and the wage bill of budget organizations. The focus on these large expenditure segments of the Russian Federation's budget was mandated by the MOF's operational needs to identify efficiency gains in these sectors and then to use the findings to extend such exercises to other sectors.